Praktik Pencegahan Keracunan Pb Pada Petugas Gardu Jalan Tol di daerah Bandung - Nurnaningsih, Hera; Setyaningsih, Yuliani; Lestantyo, Daru (Jurnal Promosi Kesehatan Indonesia, 2011)
The officers of substation highway is one of the very risky exposure to the effects of lead, from the results of levels of Pb (Lead) in the blood of 2010 conducted by PT XXX showed that average 15.252 ug / dl. This data is above 10 ug / dl, according to Centre for Disease Control and Prevention (CDC), the concentration of Pb in blood in adults should not exceed 10 ug / dl. This study uses quantitative methods with Explanatory Research with cross sectional approach, the sample size is 36 employees of PT XXX. Results showed the majority (89%) of the respondents with Pb poisoning prevention practices are less good, that the variables of knowledge is the most influential variables on Pb poisoning prevention practices on toll road officers Bandung.